Role Conflict in Student Mothers: A Review of Challenges and Coping Strategies - Azuka, Fathya Nadira; Hildayani, Rini (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
In fulfilling their multiple roles as mothers, students, and wives, student mothers encounter a range of challenges that encompass academic responsibilities, parenting duties, and household obligations. The convergence of these roles often generates considerable pressure, which can hinder productivity across various domains and negatively impact their psychological well-being. Therefore, effective coping strategies are essential to mitigate the complexities arising from role conflict. This article presents a literature review of seven selected studies, utilizing Ferrari’s (2015) framework for narrative reviews. The study aims to elucidate the coping strategies employed by student mothers to navigate the diverse and demanding expectations associated with their multifaceted roles. Findings indicate that student mothers primarily adopt two coping strategies: problem-focused coping and emotion-focused coping. Through problem-focused coping, they directly address the root causes of challenges using planful problem-solving, involving deliberate and strategic planning, alongside seeking instrumental support to obtain practical assistance from their social environment capable of providing tangible help. Conversely, emotion-focused coping involves prioritizing emotional regulation through mechanisms such as self-control to manage stress-induced emotional reactions, accepting responsibility as acknowledgment of the consequences stemming from multiple roles, positive reappraisal to reinterpret situations constructively, and seeking emotional support to obtain broader emotional assistance, encouragement, and understanding from significant others. These strategies not only facilitate balancing academic, parenting, and household responsibilities but also help reduce the adverse effects of role strain. Consequently, the implementation of effective coping mechanisms enables student mothers to overcome role-related challenges, maintain productivity, and achieve optimal well-being.Dalam memenuhi tanggung jawab multiperan sebagai ibu, mahasiswa, dan istri, student mothers menghadapi berbagai tantangan yang mencakup aspek akademik, pengasuhan, dan rumah tangga. Kombinasi peran ini sering kali menimbulkan tekanan yang berpotensi menghambat produktivitas pada setiap peran serta memengaruhi kesejahteraan psikologis mereka. Oleh karena itu, diperlukan strategi coping yang efektif untuk membantu mereka mengatasi konflik peran yang kompleks. Artikel ini menyajikan tinjauan literatur terhadap tujuh artikel yang dipilih menggunakan pendekatan framework for narrative reviews dari Ferrari (2015). Penelitian ini bertujuan untuk menggambarkan upaya student mothers dalam menerapkan strategi coping dalam menghadapi berbagai tuntutan peran yang beragam dan menantang. Hasil analisis menunjukkan bahwa student mothers mengadopsi dua jenis strategi coping utama, yaitu problem-focused coping dan emotion-focused coping. Pada problem-focused coping, mereka berupaya mengatasi sumber masalah secara langsung melalui planful problem-solving dengan perencanaan yang matang dan strategis, serta seeking instrumental support untuk mendapatkan dukungan praktis dari lingkungan sekitar untuk memberikan bantuan konkret. Sementara itu, dalam emotion-focused coping, mereka berfokus pada pengelolaan emosi melalui berbagai cara, seperti self-controlling untuk mengendalikan reaksi emosional terhadap tekanan, accepting responsibility dalam menerima konsekuensi dari peran ganda yang dijalani, positive reappraisal dalam memaknai situasi secara positif untuk menjaga motivasi, serta seeking emotional support sebagai upaya mendapatkan dukungan emosional dari orang-orang terdekat. Temuan ini dapat diterapkan oleh student mothers agar siap menghadapi berbagai tantangan, mempertahankan produktivitas, dan mencapai kesejahteraan secara optimal dalam setiap peran yang dijalani.